Village and age based precision mapping of schistosomiasis and soil-transmitted helminths in Chevakadzi ward of Shamva district in Zimbabwe - Nicholas Midzi; Masceline Jenipher Mutsaka-Makuvaza; Shan Lv; Qin-Zhi Qiang; Hong-Mei Li; Ling Tang; Xin-lin Yu; Chang-Lian Li; Tonderai Manengureni; White Soko; Xiao-Nong Zhou; Ying-Jun Qian; et al. (Scientific Reports)
Abstract Schistosomiasis is earmarked for elimination as a public health problem, while morbidity control is a priority for soil-transmitted helminthiasis (STH) by 2030. To develop targeted interventions for the two diseases, micro-mapping and an understanding of disease transmission dynamics across different age groups are necessary. This study determined the age-stratified and ward-level prevalence of schistosomiasis and STH in Chevakadzi ward, Shamva district, Mashonaland Central province, Zimbabwe. A community-wide cross-sectional pilot study was conducted in June and July 2023 in all the 14 villages in Chevakadzi ward, targeting 1680 participants aged ≥ 1 year. Thirty households per village were selected using simple random selection method. Urine and stool samples were collected to diagnose urinary, intestinal schistosomiasis and STH using the urine filtration and Kato Katz techniques respectively. Snail surveys were conducted at identified water contact sites in each village. Intermediate host snails were assessed for human schistosome cercaria. The data were analysed using descriptive statistics, spatial autocorrelation and logistic regression. The overall ward-level prevalence of combined schistosomiasis and STH was 15.6% (95%CI 13.7–17.7) and 2.5%, (95% CI 1.7–3.7) respectively. Schistosoma mansoni prevalence was 13.3% (95% CI 11.4–15.6) while S. haematobium was 6.8% (95% CI 5.5–8.3). Adults had the highest prevalence of both forms of schistosomiasis with an overall of, 20.4% (95%CI 17.6–23.5) compared to school-aged children (SAC) [10.5%, 95%CI 7.7–14.0] and preschool-aged children (PSAC) [4.7%, 95%CI 2.1–10.1], p < 0.001. Combined schistosomiasis and single species prevalence significantly differed among villages and age groups (p < 0.05), while no significant difference was observed in the intensity of infections. The risk of infection was highest in adults (AOR: 5.1, 95%CI 2.5–14.1) and 2.5 times higher in SAC (AOR: 2.5, 95%CI 1.0–6.1) compared to PSAC. Odds of infections were high in Gonyora (AOR: 2.1, 95% CI 1.0–4.2) and Peter (AOR: 2.6, 95%CI 1.3–5.2) villages. Schistosomiasis infection was clustered at the household level (Moran’s I = 0.0573, p < 0.001). None of the snails collected in the water contact sites were infected. The study has shown that schistosomiasis is focalised at a micro-geographical scale with spatial clustering among households in the study ward. Heterogenous infection rates were noted among age groups, with adults being at high risk, emphasising the need for universal coverage of interventions as opposed to the current school-based mass drug administrations (MDA). Targeted, inclusive, and micro-level-centred approaches to effectively combat schistosomiasis are necessary. Despite the low level of STH infections in the ward, interventions are necessary to interrupt their transmission.